Gender training the Union: Tensions between demands and resistances regarding extension intervention (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This paper seeks to analyze the strategies, challenges, and resistances to incorporating a gender perspective in union spaces, based on the experience of the "Unionism, Gender, and Health" extension project from the Universidad Nacional de Mar del Plata. In this project, we conducted workshops on occupational health, care, and gender in various union spaces. This initiative was designed and carried out in collaboration with different union organizations. Although it was the unions who requested training on the topic, resistance was not long in coming. Despite this, a bond of trust was established with the unions, which allowed for various workshops where gender inequalities were discussed. Creating these types of meetings is crucial for university extension to become a space for transformative knowledge construction and an effective way to generate a real impact within union structures.
Keywords: unionism; gender; feminism; extension; resistance